ANALISIS LEVEL PROBABILISTIC THINKING ABILITY PESERTA DIDIK DALAM MENYELESAIKAN SOAL CERITA PELUANG DI SEKOLAH MENENGAH ATAS - Alifatul Muyasaroh; Emi Pujiastuti; Iqbal Kharisudin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this research is to find out the level of probabilistic thinking ability possessed by students in solving opportunity story problems in senior high schools. The survey was conducted at a high school in Semarang City with 135 students in class X. A qualitative descriptive method is used to analyze the level of probabilistic thinking ability with samples taken by grouping the results of test work based on the level of probabilistic thinking ability (subjective, transitional, informal quantitative, and numerical) obtained 3 groups, so that each group is taken 1 student, so the sample is 3 out of 135 students. Data collection was carried out through a test sheet which contained one word problem about opportunity. The results of the study show that: (1) students have difficulty recognizing events that are certain to occur and are unlikely to occur; (2) only 3 levels of probabilistic thinking ability can be achieved, including 28% subjective, 45% transitive, and 27% quantitative informal; and (3) accustoming students to solving non-routine problems can develop probabilistic thinking ability.